Audit of a cardiac screening policy for elite Australian cricketers. Issue 6 (June 2020) - Orchard, Jessica J.; Orchard, John W.; La Gerche, Andre; Kountouris, Alex; Raju, Hariharan; Young, Mark; Puranik, Rajesh; Semsarian, Chris
Abstract: Objectives: To report the compliance and results of an electrocardiogram (ECG) cardiac screening program in male and female elite Australian cricketers. Design: cross-sectional study. Methods: Elite cricketers were offered screening in accordance with Cricket Australia policy. Players who consented provided a personal and family history, physical examination and resting 12-lead ECG. An audit (1 February 2019) examined all cardiac screening records for male and female players in all Australian Cricket state squads from 16 years upwards. Data extracted from the Cricket Australia database included the number of players who underwent screening; signed waivers opting out; and had follow-up tests. ECGs were re-reviewed according to the International Criteria. Results: 710 players were included in the cohort (mean age 20.4 ± 4.9 years, 62% male). 692 (97.5%) players underwent recommended cardiac screening or signed a waiver opting out (1.1%). 173 (24.4%) players were screened (or signed a waiver) more than once. Follow-up testing was conducted for 59 (6.9%) cases. No players were excluded from sport due to a cardiac problem and no major cardiac incidents occurred to any player in the audit cohort. Review of 830 ECGs showed benign athlete heart changes, including sinus bradycardia (33.5%), left ventricular hypertrophy (16.3%), and incomplete/partial right bundle branch block (8.4%), were common but abnormal screening ECGs were uncommon (2.0%). Conclusions: An audit of a cardiac screening program in elite Australian cricketers found excellent compliance. A small proportion required follow-up testing and no player was excluded from sport due to a cardiac problem. ECG analysis suggested cricket is a sport of moderate cardiac demands, with benign athlete heart changes common.